Synthesis, characterization and antimicrobial activity of water soluble dendritic macromolecules - Tulu, Metin; Aghatabay, Naz M.; Senel, Mehmet; Dizman, Cemil; Parali, Tezcan; Dulger, Basaran (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2009)
Several families of water soluble dendrimers were synthesized based on poly (propyleneoxide) amines (Jeffamines (R)) (PI). PI-core and branched units were constructed from both methylacrylate and ethylenediamine (P-2-P-9, and generations 0-3 with - NH2, - COOH functionalities). They were characterized by elemental analysis (HA), gel permeation chromatography (GPC) , FT-IR, H-1, and C-13 NMR. The antimicrobial activities of only water soluble compounds (P-1, P-3, P-4, P-6, P-7 and P-9) were evaluated using disk diffusion method in water as well as the minimal inhibitory concentration (MIC) dilution method against 9 bacteria. The obtained results from disk diffusion method are assessed in side-by-side comparison with those of Penicillin-g, Ampicillin, Cefotaxime, Vancomycin, Oflaxacin, and Tetracyclin, well-known antibacterial agents. The results from dilution procedure are compared with Gentamycin as antibacterial and Nystatin as antifungal. The antifungal activities are reported on five yeast cultures namely, Candida albicans, Kluyveromyces fragilis, Rhodotorula rubra, Debaryomyces hansenii, and Hanseniaspora guilliermondii, and the results are referenced with Nystatin, Ketaconazole, and Clotrimazole, commercial antifungal agents. In most cases, the compounds show broad-spectrum (Gram-positive and Gram-negative bacteria) activities that are comparatively higher or equipotent to the antibiotic and antifungall agents in the comparison tests. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Antibacterial; Dendritic Jeffamines; Michael addition; Nystatin; PAMAM; POLYAMIDOAMINE PAMAM DENDRIMERS; POTENTIAL-DRUG CARRIERS; ENCAPSULATION; POLYMERS; AGENTS; Pharmacology & Pharmacy